Open and Shut: Open Access in Hybrid Educational Technology Journals 2010 – 2017 - Costello, Eamon; Farrelly, Tom; Murphy, Tony (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
Little is known about open access publishing in educational technology journals that employ a hybrid model which charges authors only if they wish to publish via gold open access. In this study we sought to address this gap in the scholarly understanding of open access publishing in hybrid journals that publish research into the intersection of education and technology. We analysed three categories of article access types: gold, green, and limited access, and collected data on their prevalence in the seven-year period from 2010-2017 across 29 journals. Data was gathered from Scopus, Unpaywall, Sherpa RoMEO, and via manual searches of the journal websites, resulting in a dataset comprising the metadata of 8,479 articles. Our findings highlight that most research remains locked behind paywalls, that open access publishing through legal means is a minority activity for the scholars involved, and that the complexity and costs of legal open access publishing in these journals may be inhibiting the accessibility of research to readers.